How Important are Pocketbook Voting, Social Preferences and Expressive Motives in Referenda? - Johannes Meya; Panu Poutvaara; Robert Schwager (CESifo Forum, 2021)
Economic models on voting usually assume that voters maximize their own material interests. Yet there is convincing evidence that people also tend to care about fairness and the common good. Furthermore, some voters may derive utility from the act of voting in a certain way, independent of whether their vote affects the actual outcome. To evaluate the importance of these motives, we studied voting in student referenda on whether to collectively purchase a public good, such as a regional train ticket. Most students voted in line with their pocketbook interests and reported that their own willingness to pay was more important in their vote choice than others' willingness to pay.
Keywords: 330